The Anatomy of a Price Cut: Discovering Organizational Sources of the Costs of Price Adjustment - Mark J. Zbaracki; Mark Bergen; Daniel Levy (Bar-Ilan University, Department of Economics, 2006)
The fact that organizations find it hard to change in response to shocks in the environment is a crucial feature of the economy. Yet we know little about why it is so difficult for organizations to adjust, and where these limitations come from. In an effort to discover some of these reasons we ground ourselves in the context of price adjustment, and present a qualitative analysis of an intensive ethnographic field study of the pricing practices at a one-billion dollar Midwestern industrial manufacturing firm and its customers. We go into depth on a specific episode, a price cut, which most vividly exemplifies the themes that emerged from our data. In the specific situation, market forces clearly dictate that the firm should cut prices, and everyone in the firm agrees with this assessment, suggesting a fairly straightforward price adjustment decision. Yet when we look deeper, and dissect how the firm implemented the price cut, we uncover a rich tapestry of frictions hidden within the organization. At their core, these frictions relate to how managers, in the context of an organization, attempt to apply the fundamental elements of economic theory. Essentially they face a series of constraints that make sense in the context of an organization trying to make these adjustments, but constraints that are rarely articulated or incorporated into economic understanding of price adjustment. We discover that the largest barriers to price adjustment are related to disputes arising from collisions between "partial models" used by different organizational participants as they confront fundamental economic issues. Often, these issues have not been settled and exist in a tenuous truce within the organization – and adjustment requires the organization to deal with them in order to react to these changes.
Keywords: E12; E31; L16; L20; M21; M31; 330; Organizational Rigidity; Organizational Cost of Price Adjustment; Menu Cost; Convex Cost of Price Adjustment; Sticky Price; Price Rigidity; Time-Dependent Model; State-Dependent Model; Colliding Partial Models; Organizational Complexity; Behavioral Theory of the Firm